Pembuatan Laporan Keuangan Berbasis Excel dan Edukasi Pajak Terhadap UMKM Florist Rend Florist - Johandri Iqbal; Junaidi; sandi saputra (LP2M Politeknik Jambi, 2026)
This study aims to analyze the condition of financial recording and tax practices in Rend Florist MSMEs in West Tanjung Jabung Regency, as well as to design and implement a simple financial reporting system based on Microsoft Excel which refers to the Indonesian Institute of Accountants through SAK EMKM. The methods which are used include observation, interviews, and direct assistance in the preparation of income statements and financial position statements. The results of the study showed that before mentoring and recording were done manually and unstructured, making it difficult to evaluate business performance and calculate taxes. The implementation of an Excel-based system helps to improve administrative order, calculation accuracy, and the separation between business and personal finance. In addition, the tax education given is able to increase understanding of Final Income Tax obligations and independent tax reporting. Thus, digitizing recording and improving financial and tax literacy contributes to professionalism, accountability, and business sustainability.